2023
DOI: 10.3390/nu15071780
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox and Mortality in Older Adults: A Systematic Review

Abstract: “Obesity paradox” describes the counterintuitive finding that aged overweight and obese people with a particular disease may have better outcomes than their normal weight or underweight counterparts. This systematic review was performed to summarize the publications related to the obesity paradox in older adults, to gain an in-depth understanding of this phenomenon. PubMed©, Embase©, and Scopus© were used to perform literature search for all publications up to 20 March 2022. Studies were included if they repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 85 publications
3
16
0
1
Order By: Relevance
“…Interestingly, in the no‐landmark analysis, individuals with normal weight and diabetes, as well as overweight individuals, showed the highest and lowest all‐cause mortality risk, respectively. This may be associated with the obesity paradox effect, which has a critical role in the incidence of a disease but a protective effect on those with a severe condition 22,23 . Yet, the mechanism behind this association remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the no‐landmark analysis, individuals with normal weight and diabetes, as well as overweight individuals, showed the highest and lowest all‐cause mortality risk, respectively. This may be associated with the obesity paradox effect, which has a critical role in the incidence of a disease but a protective effect on those with a severe condition 22,23 . Yet, the mechanism behind this association remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that regardless of the BMI estimation method, overweight older men and women have a lower mortality risk, compared to normal/underweight individuals after adjusting for confounders, such as smoking, education, physical activity, residence, marital status, and comorbidities [ 6 ]. Irrespective of the method, obesity in men and women aged ≥ 80 years did not lead to an increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, aged 65 years and over, the relationship between overweight, obesity and morbidity does not seem as clear, since earlier studies have reported that overweight and a low degree of obesity (BMI 30 - <35) have a certain protective effect against co-morbidity [ 3 , 4 ]. In addition, it has been suggested that neither overweight nor obesity increases the risk of all-cause mortality [ 5 ], particularly in the presence of comorbidities or acute medical problems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between malnutrition and ageing is well known in both CKD patients and non-CKD patients, due to shared etiologic factors, such as comorbid conditions associated with cachexia, physical inactivity, and frailty [ 25 , 27 ]. Indeed, the “obesity paradox” has been recognized in both dialysis and elderly populations, in whom overweight might be protective, paradoxically resulting in a better outcome [ 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%